Double Layer Impedance in Mixtures of Acetonitrile and Water. Issue 8 (23rd March 2018) - Aoki, Koichi Jeremiah; Chen, Jingyuan; Tang, Peng
Abstract: Double layer (DL) impedances were evaluated in mixed solutions of water and acetonitrile at various ratios in the polarized potential domain in order to find competitive orientation of the two solvent molecules on the platinum electrode. The DL capacitance at any ratio of the mixture shows the common power law of the ac‐frequency. The capacitance at molar fractions of water less than 0.2 increases linearly with the fraction, and reaches the value for aqueous solution. This variation indicates accumulation of water molecules on the electrode excluding acetonitrile molecules. It is modelled on the concept of the Langmuir‐type isotherm in which water and acetonitrile molecules have competitive interaction with the electrode. The experimental variations by the use of the isotherm yield the difference in the interaction energy, 6 kJ mol −1 . The accumulation of water in the DL is supported by the formation of the adsorbed layer by insoluble ferrocene. Abstract :